Taxonomic Revision of the Southeast Asian Ant Genus Euprenolepis - Lapolla, John S. (Zootaxa, 2009)
The taxonomy of Euprenolepis has been in a muddled state since it was recognized as a separate formicine ant genus. This study represents the first species-level taxonomic revision of the genus. Eight species are recognized of which six are described as new. The new species are E. echinata, E. maschwitzi, E. thrix, E. variegata, E. wittei, and E. zeta. Euprenolepis antespectans is synonymized with E. procera. Three species are excluded from the genus and transferred to Paratrechina as new combinations: P. helleri, P. steeli, and P. stigmatica. A morphologically based definition and diagnosis for the genus and an identification key to the worker caste are provided.